Onychomycosis due to Chaetomium globosum with yellowish black discoloration and periungual inflammation - Shi, Dongmei (Med Mycol Case Rep, 2016)
Onychomycosis is usually caused by dermatophytes, although also other filamentous and yeast-like fungi are associated with nail invasion. Chaetomium is an environmental genus of ascomycetes exhibiting a certain degree of extremotolerance. We report the first case of onychomycosis in a 46-year-old woman in China caused by Chaetomium globosum. The patient showed yellowish black discoloration with periungual inflammation on the left first toenail. We confirmed the causative agent, C. globosum, by KOH mount, culture, micromorphology and DNA sequence analysis